JENIS DAN STATUS KONSERVASI TUMBUHAN PADA JALUR LINTAS ANTAR DAERAH DI KABUPATEN TELUK WONDAMA - Maria Sadsoeitoeboen; Johanis Paulus Kilmaskossu; Fajar Ria Dwi Natalia Sianipar (FMIPA Universitas Papua, 2020)
This study aims to determine the type and status of plant conservation in the cross-regional route in Teluk Wondama Regency. The method used in this research is the transect method at 2 locations, namely Simpanggoro and Yamor. The results of this study found 193 plant species. When viewed from the benefits and stature, they were grouped into 5 groups, namely 119 tree species (45 families), 9 species of Palm (1 family), 22 species of shrubs and herbs (12 families), 10 species of lianas (6 families) and 19 types of agricultural and plantation crops (16 families). There are 4 types of Papuan plants, 2 endangered species and 2 protected plant species Regulation of the Minister of Environment and Forestry of the Republic of Indonesia, No.106 of 2018.